Time to redefine success? TICI 3 versus TICI 2b recanalization in middle cerebral artery occlusion treated with thrombectomy. (17th February 2016) - Kleine, Justus F; Wunderlich, Silke; Zimmer, Claus; Kaesmacher, Johannes
Abstract : Background: The Thrombolysis in Cerebral Infarction (TICI) scale is the most widely applied scoring system to grade technical results of recanalizing therapies in acute ischemic stroke (AIS). TICI 2b and TICI 3 are conventionally subsumed as 'successful recanalization'. Previous studies reported conflicting results for the clinical relevance of achieving complete (TICI 3) versus 'almost' complete reperfusion (TICI 2b). Objective: To examine if neurologic outcome differs significantly between TICI 2b and TICI 3 in patients with AIS with middle cerebral artery (MCA) occlusion treated 'successfully' with mechanical thrombectomy (MTE). Methods: Retrospective analysis of prospectively collected data from 352 consecutive patients with isolated MCA occlusion subjected to MTE between January 2007 and July 2015. Results: 262 of the 277 successfully treated patients had adequate follow-up and were included. Patients (n=119) in the TICI 3 group had a lower National Institutes of Health Stroke Scale score at discharge (NIHSS-DIS; median 5 vs 7, p=0.005), and showed higher rates of strong neurologic improvement (ΔNIHSS≥8 or NIHSS-DIS≤1, 68.4% vs 37.1%, p=0.002) and favorable NIHSS outcome (NIHSS-DIS≤5, 49.2% vs 31.9%, p=0.005). Hospital stays were shorter in the TICI 3 group (median 10 vs 12 days, p=0.014). After adjusting for relevant baseline and treatment parameters, TICI 3 was independently associated with strong neurologic improvement (OR=4.3, 95% CI 2.2 to 8.3, p<0.001) and favorable NIHSS outcome (OR=3.0, 95% CI 1.5 to 6.3, p=0.003). Conclusions: Neurologic outcome is substantially better in TICI 3 than TICI 2b patients, and hospital stays are shorter. Endovascular strategies that consequently strive to achieve TICI 3 may be warranted and cost-effective, and should be examined by future research. TICI 3 rates should be included as a safety measure in studies evaluating MTE devices and techniques.